Sosialisasi Mitigasi Bencana pada Daerah Rawan Longsor - Achmad Bakri Muhiddin; Nur, S. H; Harianto T; Djamaluddin R; Arsyad A; Suprapti A (Faculty of Engineering UNHAS, 2021)
Landslide vulnerability at several locations in South and West Sulawesi requires inspection and evaluation because of the failure of retaining wall structure. Some of the damage that occurs needs to be handled with technical evaluation and back analysis to find out the mechanism of the failure through site investigation, data observation from stakeholders. The main purpose of this study is to discuss and facilitated information about retaining wall design to withstand the burden and avoid repeating similar disaster in the next projects. From observations and field facts, the collapse of retaining wall is caused by the dimensions of retaining wall that are too slender so that they are unable to withstand active soil pressure when saturated soil. Retaining walls drainage does not work properly so the soil is easily saturated when it rains. The collapse was caused by the collapse of the wall and the eroding of the retaining wall foundation due to the intrusion of water in the horizontal crack at the meeting of the shoulder of the road and the retaining wall. Disaster risk management begins with the assessment and mapping of disaster risks. Learning to the community and construction service actors in disaster-prone areas is done intensively in order to be able to visually assess the threat. Mitigation efforts are more effective with disaster risk reduction investigations in the form of the implementation of early warning systems that allow relevant parties to detect early damage and make repairs before greater damage occurs.